Clinical Utility of Circulating Tumor DNA (ctDNA) in the Bloodstream as Predictive and Prognostic Biomarkers in Breast Cancer Management - Densingh Johnrose; Azaruddin Gohil (Archives of Current Research International, 2025)
Background: Breast cancer remains one of the most prevalent malignancies among women worldwide, with early detection and individualized treatment significantly improving patient outcomes. In recent years, biomarkers have emerged as pivotal tools in enhancing diagnostic precision, predicting therapeutic response, and monitoring disease progression. Among these, circulating tumor DNA (ctDNA) and liquid biopsy techniques have gained substantial attention due to their non-invasive nature and potential to provide real-time insights into tumor dynamics. Objective: This review aims to evaluate the clinical utility of liquid biopsy and ctDNA as predictive and prognostic biomarkers in breast cancer management. Methods: A comprehensive literature review was conducted using peer-reviewed publications from databases such as PubMed, Scopus, and Web of Science. Studies were selected based on relevance, recency, and clinical significance, focusing on techniques for ctDNA extraction, quantification, and mutational analysis, including digital PCR and next-generation sequencing. Results/Findings: Emerging evidence highlights that ctDNA can reflect tumor heterogeneity, detect minimal residual disease (MRD), and predict relapse earlier than traditional imaging methods. Liquid biopsy offers a less invasive alternative for molecular profiling and treatment monitoring, especially in metastatic settings. Mutations in genes such as PIK3CA, ESR1, and TP53 detected through ctDNA have been correlated with resistance to endocrine therapy and targeted agents, aiding in treatment planning. Conclusion: Liquid biopsy and ctDNA analysis represent a transformative approach in the precision medicine landscape of breast cancer. Their integration into clinical practice may optimize patient stratification, therapeutic decision-making, and surveillance. However, standardization of methods and validation through large-scale clinical trials are essential for routine implementation.